ASXL1 mutations predict inferior molecular response to nilotinib treatment in chronic myeloid leukemia - Schönfeld, Lioba; Rinke, Jenny; Hinze, Anna; Nagel, Saskia N.; Schäfer, Vivien; Schenk, Thomas; Fabisch, Christian; Brümmendorf, Tim Henrik; Burchert, Andreas; le Coutre, Philipp; Krause, Stefan W.; Saußele, Susanne; et al. (Leukemia, 2022)
Gene mutations independent of BCR::ABL1 have been identified in newly diagnosed patients with chronic myeloid leukemia (CML) in chronic phase, whereby mutations in epigenetic modifier genes were most common. These findings prompted the systematic analysis of prevalence, dynamics, and prognostic significance of such mutations, in a clinically well-characterized patient population of 222 CML patients from the TIGER study (CML-V) by targeted next-generation sequencing covering 54 myeloid leukemia-associated genes. In total, 53/222 CML patients (24%) carried 60 mutations at diagnosis with ASXL1 being most commonly affected (n = 20). To study mutation dynamics, longitudinal deep sequencing analysis of serial samples was performed in 100 patients after 12, 24, and 36 months of therapy. Typical patterns of clonal evolution included eradication, persistence, and emergence of mutated clones. Patients carrying an ASXL1 mutation at diagnosis showed a less favorable molecular response to nilotinib treatment, as a major molecular response (MMR) was achieved less frequently at month 12, 18, and 24 compared to all other patients. Patients with ASXL1 mutations were also younger and more frequently found in the high risk category, suggesting a central role of clonal evolution associated with ASXL1 mutations in CML pathogenesis.
Gesehen am 02.10.2023